The Dilemma of Peri-Procedural Warfarin Management: A Narrative Review - Islam Eljilany (14151588) (2021)
Periprocedural vitamin K antagonist management is a complex process and inherently entails multiple clinical issues. Marked variations have been reported in different aspects of this process. These differences were noted at the clinician and institutional levels owing to the lack of evidence-based data leading to many discrepancies in decision-making. This review aims to address the gap of vitamin K antagonist periprocedural management acknowledged by previously published prescribers’ questionnaires. One of the components of this process is “bridging,” which aims to provide minimal interruption of the anticoagulation period through the use of heparin products. Recent studies showed that bridging is increasing bleeding risk. Secondly, interruption decision relies on the classification of thromboembolism risk which depends on trials that did not include patients with atrial fibrillation. Thirdly, the interruption duration is different among different International normalization ratio levels, which strengthens the difference in the clinical practice of preoperative vitamin K antagonist management. Lastly, the resumption of a vitamin-K antagonist after surgery has many scenarios according to the procedure and patient risk of bleeding. Vitamin-K antagonist periprocedural management is complicated due to individual practice and the lack of strictly implemented institutional standardized protocols to guide, manage and evaluate the process. Other Information Published in: Clinical and Applied Thrombosis/Hemostasis License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/10760296211012093